PALYNOFACIES STUDIES OF THE LATE CRETACEOUS (TURONIAN-MAASTRICHTIAN) STRATA FROM JAURO JATAU, GONGOLA SUB-BASIN, NORTHERN BENUE TROUGH, NIGERIA - Aliyu, Abdulkarim Haruna; Maigari, Abubakar Sadiq; Umar, Bappah Adamu; Nabage, Nuru Abdullahi; Shirputda, John Jitong; Saidu, Fatima; Mohammed, Mohammed (FUDMA JOURNAL OF SCIENCES, 2024)
Geographically located within Gombe, Bauchi, and Yobe states, the Gongola Sub-basin has drawn attention from several academics looking to increase Nigeria's oil reserves relative to the inland frontier basins. This paper's goal is to determine the thermal maturity of strata from drill samples of the Fika shales in Nigeria's Northern Benue Trough, Gongola Sub-basin. To predict the well section's maturity and kerogen type, this study uses optical and organic facies studies. Twenty-seven samples of ditch cuttings were prepared using the universally accepted acid palynological procedure. The dispersed mounted slides revealed a variety of pollen, spores, and palynomacerals upon microscopic inspection. The well section under study exhibits a range of thermal maturation from mature to late mature, indicating the possibility of producing oil and gas. This corresponds to a range of thermal alteration values of 4 – 6 and equivalent vitrinite reflectance (%Ro) values of 0.6% – 1.35%. The total recovered Sedimentary Organic Matter (SOM) in this study was classified into Palynomorphs, Amorphous Organic Matter (AOM) and Phytoclasts and plotted on a ternary graph. The Percentage frequencies of AOM, Phytoclast and Palynomorphs were compared with the zones of the Tyson Ternary diagram. Most of the distribution frequencies lie within zones II, IX, VI and Iva suggesting Kerogen types III (gas-prone) and II (oil-prone).
Keywords: Palynofacies; Thermal maturity; Kerogen Type; Gongola Basin